2014
DOI: 10.3889/oamjms.2014.022
|View full text |Cite
|
Sign up to set email alerts
|

HCV Seroconversion in two Egyptian Hemodialysis Units: Role of Detection Method and Patients Isolation

Abstract: Background: Hepatitis C virus (HCV) infection is a significant cause of morbidity and mortality in end stage renal disease (ESRD) patients on hemodialysis (HD). Routine HCV viremia screening is recommended in those patients but it is not applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…This was agreed by Egyptian study compare between centers uses isolation of HCV positive patients and others don't, and found that seroconversion seen only in units not use isolation [17]. Other studied in Egypt in three different governorates found that incidence of HCV seroconversion is significantly lower in the group of patients within units implementing isolation programs of the HCV infected patients [32].…”
Section: Discussionsupporting
confidence: 56%
“…This was agreed by Egyptian study compare between centers uses isolation of HCV positive patients and others don't, and found that seroconversion seen only in units not use isolation [17]. Other studied in Egypt in three different governorates found that incidence of HCV seroconversion is significantly lower in the group of patients within units implementing isolation programs of the HCV infected patients [32].…”
Section: Discussionsupporting
confidence: 56%
“…Studies show that early diagnosis not only enables appropriate treatment to those who require but also plays a major role in infection control. 13 Pre-Op and Post-Op measures thereby also include Isolation of HCV positive patients in High dependency units to protect them from transmission before and after surgery. 14 It also includes multiple Blood transfusions which is already a common practice in patients on Chronic end stage renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Common risk factors associated with HCV transmission are injection drug use as in addicts, organ transplantation such as liver or kidney, blood and blood product transfusion commonly seen in anemia, long term hemodialysis, occupational exposure to viruses seen in health care workers of HCV, infected therapeutic injections and major & minor surgeries with screening for HCV, dental treatment with non-sterilized equipment, shaving at barber shops without changing old blades and having multiple cuts during the shaves, unprotected sexual contact without using barrier method and vertical transmission from mother - ------------------------------------------------------------------------------Received on 15-01-2021 Accepted on 11-06-2021 to child 5 . The phase before the seroconversion after being inoculated with HCV usually last to about 2 months in immunocompetent subjects and may last for 6-12 months in immune compromised subjects 7 . Hepatitis C virus (HCV) remains the leading cause of liver cirrhosis in patients with chronic kidney disease including patients on long-term hemodialysis.…”
Section: Introductionmentioning
confidence: 99%